Evidence of Local Concentration of α-Particles from (211)At-Labeled Antibodies in Liver Metastasis Tissue - Kodaira, Satoshi (J Nucl Med, 2019)
We investigated the local concentration of α-particles from (211)At-labeled trastuzumab antibodies against human epidermal growth factor receptor type 2 antigens in liver metastasis tissue of mice. Methods: Mice carrying metastatic cancer in their liver were injected with (211)At-agent. After 12 h, the liver was removed and sliced, and 2 tissue samples of liver tissues without lesions and one containing metastatic lesions were mounted on the CR-39 plastic nuclear track detector. Microscope images of the tissues on the CR-39 were acquired. After irradiation for 31 h, the tissues were removed from the CR-39. A microscope image of α-particle tracks on the CR-39 was acquired after chemical etching. The positions of each tissue sample and the emitted α-particle tracks were adjusted to the same coordinates. Results: The positional distribution of α-particle tracks emitted from (211)At was consistent within the tissue. The α-particle tracks were mainly allocated in the tumor region of the tissue. The absorbed dose in individual cells segmented by 10-μm intervals was obtained by the spectroscopic analysis of the linear-energy-transfer spectrum. The concentration efficiency—the track density ratio of α-particle tracks in the necrotized tissue, which was the tumor region, to the normal tissue—was found to be 6.0 ± 0.2. In the tumor region, the high–linear-energy-transfer α-particles deposited a large enough dose to cause lethal damage to the cancer cells. Conclusion: The total absorbed dose ranged from 1 to 7 Gy with a peak at around 2 Gy, which would correspond to a 2–3 times higher biologically equivalent dose because of the high relative biological effectiveness of the α-particles emitted from (211)At.